(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2024)
Entrepreneurship, a dynamic concept developing innovation, risk-taking, and creativity, finds diverse expressions in today’s complicated business landscape. One unavoidable fact is women’s entrepreneurship, gaining momentum as a critical theme in contemporary women entrepreneurship discourse. This research focuses on the critical dimensions and factors influencing women’s entrepreneurial pursuits, specifically within the context of Nawalparasi District. Applying a quantitative research approach and survey study through a Google Forms questionnaire, we collected data from a sample population of one hundred fifty (N = 150) women entrepreneurs in Nawalparasi via a simple random sampling method. Principal Component Analysis was applied for factor reduction and then Binary Logistic Regression was used to find the impact of different influencing factors on women entrepreneurship. The findings indicate significant associations between different influencing factors and women’s entrepreneurship in Gaidakot, Nawalparasi. The results further show that limited access to finance, inherent sociocultural norms, gaps in education and training, regulatory constraints, and disparities in technological access were crucial factors. The findings hold substantial implications for policymakers, researchers, teachers, students, and advocates for gender equality, serving as a catalyst to motivate and empower women entrepreneurs in Nawalparasi. By addressing the above mentioned factors, our research contributes to fostering a more inclusive and supportive entrepreneurial ecosystem, thereby advancing both economic development and gender equity in the region.